THE EFFECT OF JIGSAW II MODEL ON STUDENTS’ READING COMPREHENSION ACHIEVEMENT (A STUDY AT THE TENTH GRADE STUDENTS OF SMA SWASTA HARAPAN PADANGSIDIMPUAN 2017/2018 ACADEMIC YEAR) - Salmia Siregar (JURNAL LINER (Language Intelligence and Educational Research), 2019)
Abstract: The aims of the research is to know the application of jigsaw II model on students’ reading comprehension achievement at the tenth grade of SMA Swasta Harapan Padangsidimpuan, to know before and after jigsaw II model at the tenth grade of SMA Swasta Harapan Padangsidimpuan, and to know whether there is any significant effect of jigsaw II model on students’ reading comprehension achievement at the tenth grade of SMA Swasta Harapan Padangsidimpuan 2017/2018 Academic Year. The population in this research is all of the tenth grade students are 37. The sample are 37 students which taken by total sampling.The research method is use by experimental method. Collecting the data by observation sheet and test as an instrument. The result mean score of the application jigsaw II model is 3.2, based on the technique of analysis data the criterion of score jigsaw II model with categorized “Very Good”. The result of students reading comprehension the text before taught by using jigsaw II model is 63,51. The category is “Enough”.The result of students reading comprehension the text after taught by using jigsaw II model is 74.71. The category is “Good”.The average To know the result of the data, the researcher analysis data by use the formula of ttest. The result of the data analysis show that of ttest = 3.20,meanwhile ttable 2.72. It means that ttest is higher than ttable. So, the hypothesis is accepted. It means that there is significant effect of jigsaw II model on students’ reading comprehension achievement at the tenth grade of SMA Swasta Harapan Padangsidimpuan.